Effects of commercial layer feed supplementation on haematological and reproductive parameters of indigenous duck in rural area (International Journal of Natural Sciences, 2016)
This study was carried out to evaluate the effects of supplementation of commercial layer feed on body weight, egg production and haematological profile of the laying ducks rearing under the rural condition of Bangladesh. Twenty indigenous ducks (Khaki Campbell x Local duck) of 24 weeks old was selected from a farm and randomly divided into four equal groups (n=5) and numbered as group T0, T1, T2 & T3. The different amount of feed was supplied into four groups for three months. The all four groups (T0, T1, T2 and T3) were fed with routine feeding in scavenging condition. But T1 group supplemented with 120 gm, T2 group 60 gm and T3 group 30 gm of commercial feed. Significant differences were found in both egg production and haematological profile of ducks in compared to control group. Egg production was significantly (P